Laser diode irradiation mitigates salt stress in rice through coordinated physiological and molecular responses - Cheng, Feng; Qi, Yetong; Lei, Kangqi; Yang, Han; Lei, Yumeng; Ahmed, Temoor; Qi, Xingjiang; Li, Zhitao (Frontiers in Plant Science, 2025)
Soil salinization affects approximately 20% of cultivated land globally, posing significant threats to rice production and food security. Although conventional approaches have been attempted to enhance salt tolerance in rice, several issues have arisen, such as high costs, complexity and application challenges. The potential of laser diode (LD) technology to enhance plant resilience to salinity stress remains underexplored. This study investigated the potential of red-blue LD at a 3:1 ratio and intensities of 5, 10, or 15 μmol m−2 s−1 PPFD on salt tolerance in rice seedlings using integrated phenotypic, physiological, transcriptomic, and metabolomic analyses. LD-treated seedlings exhibited significantly enhanced growth parameters, including increased plant height, stem diameter, and root morphology as compared with control. Photosynthetic efficiency was substantially improved, with elevated chlorophyll content and enhanced gas exchange parameters. LD treatment maintained ionic homeostasis by reducing Na+ accumulation while preserving K+ content, resulting in lower Na+/K+ ratios. Notably, LD treatment at 15 μmol m−2 s−1 PPFD substantially enhanced the antioxidant enzyme activities such as SOD (63%), POD (62%), CAT (54%), and APX (14%) in rice leaves as compared to control. Correspondingly, oxidative damage markers were significantly reduced, with H2O2 and MDA levels decreased while proline accumulation increased. Transcriptome sequencing analysis showed that the application of red-blue laser upregulated the expression of genes related to regulatory pathways such as photosynthesis (OsLhca and OsLhcb), ion homeostasis (OsNHX, OsHKT and OsHAK), and antioxidant defense (OsSOD, OsPOD, OsCAT and OsAPX). Metabolomic profiling identified enhanced phenylpropanoid biosynthesis, glutathione metabolism, and flavonoid accumulation as key protective mechanisms. This research demonstrates that red-blue LD irradiation represents a promising sustainable technology for enhancing crop resilience to salinity stress through coordinated physiological and molecular responses.